Faktor Risiko Terjadinya Covid-19 Pada Penderita Diabetes Melitus Tipe 2 - Apin A. Panua; Ricky Zainuddin; Ekayanti Hafidah Ahmad; Fitriani Sangkala (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: Covid-19 is an infectious disease that first appeared in the city of Wuhan, China, and was caused by SARS-CoV-2. This literature review aims to identify risk factors for the occurrence of Covid-19 in patients with type 2 DM. Methods: Analytical descriptive literature review design. Data obtained through article search results using five electronic databases namely Pubmed, ProQuest, ScienceDirect, Cochrane Library, and Google Scholar identified 10,951 articles with a total sample of 5,464,617 respondents. The analysis uses a map of the extracted data in a grid synthesis table including author, year of publication, country, purpose, sample, design, duration, results, and conclusions of the study. Results: The six articles identified in this review showed that one study reported risk of developing COVID-19 in patients with type 2 diabetes 1,369 times, one study 2,180 times, one study 4.7 times, and another study up to 16.5 times. Patients who are male and aged 53 years have a risk of 1.395 times higher than those who are younger and female. Conclusion: Patients with type 2 diabetes have a significantly higher risk of contracting Covid-19 compared to people without diabetes, especially in patients aged 53 years and male.